Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : Art centres Stuttgart / Karlsruhe - Münich. - Adriani, Götz (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1978)
Antes, Horst ; Dahmen, Karl Fred ; Fruhtrunk, Günter ; Geiger, Rupprecht ; Graevenitz, Gerhard von ; Hajek, Otto Herbert ; Hauser, Erich ; Heider, Klaus ; Hoflehner, Rudolf ; Hrdlicka, Alfred ; Hüppi, Alfonso ; Jochims, Raimer ; Krieg, Dieter ; Lenk, Kaspar Thomas ; Pfahler, Georg Karl ; Quinte, Lothar ; Sonderborg, K.R.H. ; Wittenborn, Rainer
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland; Stuttgart; Karlsruhe; München